Effects of kenaf loading and alkaline treatment on properties of kenaf filled natural rubber latex foam - Ahmad Fikri Abdul Karim; Hanafi Ismail; Zulkifli Mohamad Ariff (Penerbit Universiti Kebangsaan Malaysia, 2018)
This research was carried out to study the effects of kenaf loading and alkaline treatment on tensile properties, density, thermal and morphological properties of kenaf filled natural rubber latex foam (NRLF). Samples were prepared using a Dunlop method. From the results, increasing loading of kenaf reduced the tensile strength and elongation at break for both samples, treated and untreated kenaf filled NRLF. Meanwhile, modulus at 100% elongation and density increased with an increased in kenaf loading. Samples with treated kenaf showed higher tensile strength, modulus at 100% elongation and density but low in elongation at break as compared with samples with untreated kenaf. Thermal study by using thermogravimetric analysis (TGA) showed that thermal stability reduced with increased in kenaf loading for both samples. Samples with treated kenaf have higher thermal stability compared with samples of untreated kenaf. The filler-matrix interaction and the pores size variation of both samples was clearly seen in the micrograph images by using scanning electron microscope (SEM).